2011
DOI: 10.1186/1471-2377-11-157
|View full text |Cite
|
Sign up to set email alerts
|

The odor stick identification test for Japanese differentiates Parkinson's disease from multiple system atrophy and progressive supra nuclear palsy

Abstract: BackgroundProgressive supranuclear palsy (PSP) and parkinsonian variant of multiple system atrophy (MSA-P) are clinically difficult to differentiate from idiopathic Parkinson's disease (PD), particularly in the early stages of the disease. Previous reports indicated that the olfactory function is relatively intact or slightly reduced in patients with PSP and MSA-P, suggesting that the odor stick identification test for Japanese (OSIT-J), which is a short and simple noninvasive test that is potentially useful c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 33 publications
1
22
1
1
Order By: Relevance
“…A published meta‐analysis combining studies with smaller numbers of patients could substitute for one qualifying study (two other studies with >30 patients in each group are still required). Currently, olfactory loss and metaiodobenzylguanidine scintigraphy meet this threshold, but others may eventually qualify. Note that although dopaminergic neuroimaging can help distinguish parkinsonism (ie, degeneration of the nigrostriatal system) from PD‐mimics without parkinsonism (eg, essential tremor), it does not qualify as a criterion for the differentiation of PD from other parkinsonian conditions like atypical parkinsonian syndromes.…”
Section: Criteria Benchmark—the Expert Examinationmentioning
confidence: 99%
“…A published meta‐analysis combining studies with smaller numbers of patients could substitute for one qualifying study (two other studies with >30 patients in each group are still required). Currently, olfactory loss and metaiodobenzylguanidine scintigraphy meet this threshold, but others may eventually qualify. Note that although dopaminergic neuroimaging can help distinguish parkinsonism (ie, degeneration of the nigrostriatal system) from PD‐mimics without parkinsonism (eg, essential tremor), it does not qualify as a criterion for the differentiation of PD from other parkinsonian conditions like atypical parkinsonian syndromes.…”
Section: Criteria Benchmark—the Expert Examinationmentioning
confidence: 99%
“…Thus, olfactory tests have been reported to be useful in differentiating PD from other atypical parkinsonian syndromes (APSs), such as multiple system atrophy (MSA) and progressive supranuclear palsy (PSP) [68]. …”
Section: Introductionmentioning
confidence: 99%
“…NMS may provide clues to clinicians for the differential diagnosis of parkinsonian syndrome at onset. Olfactory loss (in the anosmic or clearly hyposmic range, adjusted for age and sex) has been included as an ancillary test in support of the PD diagnosis, because studies demonstrated specificity greater than 80% for differential diagnosis with other parkinsonian conditions . Another innovation promoted by MDS PD criteria is the inclusion of NMS among the red flags or warning signs, raising the clinical suspicion of an alternative diagnosis.…”
Section: Diagnostic Phasementioning
confidence: 99%
“…Olfactory loss (in the anosmic or clearly hyposmic range, adjusted for age and sex) has been included as an ancillary test in support of the PD diagnosis, because studies demonstrated specificity greater than 80% for differential diagnosis with other parkinsonian conditions. [49][50][51][52][53][54][55][56] Another innovation promoted by MDS PD criteria is the inclusion of NMS among the red flags or warning signs, raising the clinical suspicion of an alternative diagnosis. As such, although the absence of NMS suggests a PD-mimicking, nonparkinsonian condition, the excessive severity of specific NMS (such as autonomic failure) suggests an atypical parkinsonism (e.g., multiple system atrophy [MSA]).…”
Section: Clinical Biomarkersmentioning
confidence: 99%